Sensitivity and Negative Predictive Value of Motor Evoked Potentials of the Facial Nerve - Bovo, Nicolas; Momjian, Shahan; Gondar, Renato; Bijlenga, Philippe; Schaller, Karl; Boëx, Colette (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Objective The objective of this study was to determine the performance of the standard alarm criterion of motor evoked potentials (MEPs) of the facial nerve in surgeries performed for resections of vestibular schwannomas or of other lesions of the cerebellopontine angle.Methods This retrospective study included 33 patients (16 with vestibular schwannomas and 17 with other lesions) who underwent the resection surgery with transcranial MEPs of the facial nerve. A reproducible 50% decrease in MEP amplitude, resistant to a 10% increase in stimulation intensity, was applied as the alarm criterion during surgery. Facial muscular function was clinically evaluated with the House–Brackmann score (HBS), pre- and postsurgery at 3 months.Results In the patient group with vestibular schwannoma, postoperatively, the highest sensitivity and negative predictive values were found for a 30% decrease in MEP amplitude, that is, a criterion stricter than the 50% decrease in MEP amplitude criterion, prone to trigger more warnings, used intraoperatively. With this new criterion, the sensitivity would be 88.9% and the negative predictive value would be 85.7%. In the patient group with other lesions of the cerebellopontine angle, the highest sensitivity and negative predictive values were found equally for 50, 60, or 70% decrease in MEP amplitude. With these criteria, the sensitivities and the negative predictive values would be 100.0%.Conclusion Different alarm criteria were found for surgeries for vestibular schwannomas and for other lesions of the cerebellopontine angle. The study consolidates the stricter alarm criterion, that is, a criterion prone to trigger early warnings, as found previously by others for vestibular schwannoma surgeries (30% decrease in MEP amplitude).
Keywords: intraoperative neuromonitoring; facial nerve; cerebellopontine angle; motor evoked potentials; vestibular schwannomas